Metodología y buena gestión de emergencias : elementos fundamentales Guía de preparación para emergencias zoonitarias - Honhold, Nick; Douglas, Ian; Geering, William; Shimshoni, Arnon; Lubroth, Juan (FAO, 2019)
Salud animal